2009
DOI: 10.1161/circresaha.109.200568
|View full text |Cite
|
Sign up to set email alerts
|

Aldose Reductase Protects Against Early Atherosclerotic Lesion Formation in Apolipoprotein E-Null Mice

Abstract: Rationale Atherosclerotic lesion formation is associated with the accumulation of oxidized lipids. Products of lipid oxidation, particularly aldehydes, stimulate cytokine production and enhance monocyte adhesion, however their contribution to atherosclerotic lesion formation remains unclear. Objective To test the hypothesis that inhibition of aldehyde removal by aldose reductase (AR), which metabolizes both free and phospholipid aldehydes, would exacerbate atherosclerotic lesion formation. Methods and Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
66
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 40 publications
(63 reference statements)
2
66
0
Order By: Relevance
“…For example, in LDL-R null mice, inhibition of NF-B in macrophages decreases atherosclerotic lesion formation ( 56 ), whereas IL-6-null mice develop more fatty streaks than WT mice ( 57 ). Similarly, despite the clear infl ammation-enhancing effects of PLA 2 and AR in macrophages reported here, atherosclerotic lesion formation is higher in AR-and apoEnull mice than it is in WT-apoE-null mice ( 58 ), and Lp-PLA 2 gene transfer reduces spontaneous atherosclerosis ( 46 ). Clearly, extensive additional investigations are required to fully understand how infl ammation contributes to atherosclerotic lesion formation and how it is triggered by oxidized phospholipids and regulated by their metabolism.…”
Section: Discussionmentioning
confidence: 54%
“…For example, in LDL-R null mice, inhibition of NF-B in macrophages decreases atherosclerotic lesion formation ( 56 ), whereas IL-6-null mice develop more fatty streaks than WT mice ( 57 ). Similarly, despite the clear infl ammation-enhancing effects of PLA 2 and AR in macrophages reported here, atherosclerotic lesion formation is higher in AR-and apoEnull mice than it is in WT-apoE-null mice ( 58 ), and Lp-PLA 2 gene transfer reduces spontaneous atherosclerosis ( 46 ). Clearly, extensive additional investigations are required to fully understand how infl ammation contributes to atherosclerotic lesion formation and how it is triggered by oxidized phospholipids and regulated by their metabolism.…”
Section: Discussionmentioning
confidence: 54%
“…This conjugative reaction is further enhanced by glutathione S-transferases. Our previous studies have shown that the glutathione conjugates of aldehydes are further metabolized by a reductive transformation catalyzed by aldose reductase (AR) (17,18) and that inhibition of this metabolic transformation increases aldehyde accumulation and exacerbates ischemic injury (19) and atherosclerotic lesion formation (6). These observations support the view that reduction diminishes the ability of aldehyde-glutathione conjugates to induce tissue toxicity.…”
mentioning
confidence: 73%
“…These aldehydes react readily with cellular nucleophiles such as glutathione, histidine, lysine, or arginine residues in proteins and guanosine bases in DNA. Previous studies have shown that aldehyde-modified proteins accumulate in diseased tissue during atherosclerosis (5,6), myocardial ischemia (7,8), arteritis (9), diabetes, and Alzheimer (10) and Parkinson (11,12). Increased accumulation of aldehyde-modified DNA bases has also been associated with oxidative stress (13)(14)(15).…”
mentioning
confidence: 99%
“…Blood was collected every 4 weeks from the tail vein after a 6-hour fast, and blood glucose was measured by an ACCU-CHEK Aviva glucometer. Levels of cholesterol and triglycerides in the plasma were measured as described (61,62). For the quantitation of cholesterol and triglycerides in the liver, the tissue was pulverized and lipids were extracted as described by Bligh and Dyer (63).…”
Section: Methodsmentioning
confidence: 99%